Sharps, flats, and scribes: "musica ficta" in the Machaut manuscripts. Volume I: text, Volume II: edition - Harden, Bettie Jean (Michigan University microfilms international, 1986)
A Thesis presented to the Faculty of the Graduate School of Cornell Univesity in Partial Fulfillment of the Enquirements for the Degree of Doctor of Philosophy, 1983